Bio-fabricated zinc oxide nanoparticles mediated by endophytic fungus Aspergillus sp. SA17 with antimicrobial and anticancer activities: in vitro supported by in silico studies - Abdelrahman, Sally El Said Abo Halawa; El Hawary, Seham; Mohsen, Engy; El Raey, Mohamed A.; Selim, Heba Mohammed Refat M.; Hamdan, Ahmed M. E.; Ghareeb, Mosad A.; Hamed, Ahmed A. (Frontiers in Microbiology, 2024)
In recent years, the world's attention has been drawn to antimicrobial resistance (AMR) because to the frightening prospect of growing death rates. Nanomaterials are being investigated due to their potential in a wide range of technical and biological applications. The purpose of this study was to biosynthesis zinc oxide nanoparticles (ZnONPs) using Aspergillus sp. SA17 fungal extract, followed by characterization of the produced nanoparticles (NP) using electron microscopy (TEM and SEM), UVanalysis, X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FT-IR). The HR-TEM revealed spherical nanoparticles with an average size of 7.2 nm, and XRD validated the crystalline nature and crystal structure features of the generated ZnONPs, while the zeta potential was 18.16 mV, indicating that the particles' surfaces are positively charged. The FT-IR was also used to identify the biomolecules involved in the synthesis of ZnONPs. The antibacterial and anticancer properties of both the crude fungal extract and its nano-form against several microbial strains and cancer cell lines were also investigated. Inhibition zone diameters against pathogenic bacteria ranged from 3 to 13 mm, while IC50 values against cancer cell lines ranged from 17.65 to 84.55 M. Additionally, 33 compounds, including flavonoids, phenolic acids, coumarins, organic acids, anthraquinones, and lignans, were discovered through chemical profiling of the extract using UPLC-QTOF-MS/MS. Some molecules, such pomiferin and glabrol, may be useful for antibacterial purposes, according to in silico study, while daidzein 4'-sulfate showed promise as an anti-cancer metabolite.